Woman walks ahead [videorecording (DVD)] - Chastain, Jessica, 1977-; Greyeyes, Michael; Krause, Louisa, 1986-; Rockwell, Sam (Lionsgate, 2018)
Catherine Weldon, a portrait painter from 1890s Brooklyn, travels to North Dakota to paint a portrait of Chief Sitting Bull and becomes embroiled in the Lakota peoples' struggle over the rights to their land.